160k views
4 votes
If f(x) =-4x-4 and g(x) =x^3 what is (g’f)(-2) I wrote it out as best as I could. Please help!

If f(x) =-4x-4 and g(x) =x^3 what is (g’f)(-2) I wrote it out as best as I could. Please-example-1
User Paulius
by
5.4k points

2 Answers

2 votes
64 is the correct answer!!!!!!!!
User TheCuriousOne
by
4.8k points
1 vote

Answer:

64

Explanation:

Evaluate f(- 2) then substitute the value obtained into g(x), that is

f(- 2) = - 4(- 2) - 4 = 8 - 4 = 4, then

g(4) = 4³ = 64

User Chris Tickner
by
4.7k points